Peningkatan Hasil Belajar Peserta Didik dalam Pembelajaran PKN Menggunakan Model Picture And Picture di Kelas IV SD - Putri, Nela Eka; Reinita, Reinita; Muhammadi, Muhammadi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The aim of the research is to improve the students’ learning outcome in civics subject by using Picture And Picture at 4th grade of SDN 09 Koto Luar,padang. The classroom-action research is conducted in the research by using both qualitative and qualitative approaches. The subjects of the research were the teacher and 29 students of the school (17 male students,and 12 female students).this research was conducted in two cycles where each cycle consists of planning,acting,observing and reflecting. The results of the research shows that there are an improvemrnt:a)the Lesson plan increased from 71,4%% ii cycle i to 92,8% in cycle II: b) the teacher’s aspect increased from 80,5% in cycle i to 97,2% incycle II: the students’ learning aspect also increased from 83,3% in cycle i to 94,4% in cycle II: c) the students’ learning outcome increased from 63,8 in cycle i to 84,5 in cycle II. Thus, the use of picture and picture model has improved the students’ learning outcome in learning civics subject at 4th grade of SDN 09 Koto Luar, padang.Key words: Learning outcomes, civic subject,Picture And Picture